(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Children with Attention Deficit Hyperactivity Disorder (ADHD) often struggle with maintaining attention, which can hinder their academic performance and social interactions. This study delves into the neurological underpinnings of ADHD that contribute to attention deficits and evaluates various interventions aimed at improving focus. By reviewing current literature and analyzing case studies, the research identifies effective strategies, including behavioral therapies, educational modifications, and medication. The findings highlight the importance of personalized approaches to support children with ADHD, offering practical recommendations for educators and parents. The study underscores the need for ongoing research to further enhance understanding and treatment of attention span issues in children with ADHD.